Claudin-9 enhances the metastatic potential of hepatocytes via Tyk2/Stat3 signaling - Liu, Hongyu; Wang, Min; Liang, Na; Guan, Lianyue (Turkish Journal of Gastroenterology, 2019)
Background/Aims: We have previously identified a tight junction protein claudin-9 (CLDN9) as an upregulated gene in hepatocellular carcinoma (HCC) through an immunohistochemistry analysis. Here, we explore its function and clinical relevance in human HCC. Materials and Methods: Stable transfection of the hepatocyte line HL7702 with CLDN9 was confirmed by the real-time polymerase chain reaction (PCR), western blotting, and immunofluorescence. The impact of CLDN9 on the cell invasion and migration was assessed in vitro by a transwell assay and wound-healing experiment. Western blotting was used to determine the activation state of the Tyk2 (tyrosine kinase 2)/Stat3 (signal transducer and activator of transcription 3) pathway. Moreover, we used a Tyk2-RNAi assay to silence the expression of Tyk2 in CLDN9 expressing hepatocytes; subsequently, the impact of the Tyk2/Stat3 signaling pathway on the cell invasion and migration in vitro was assessed by a transwell assay and a wound-healing experiment. Furthermore, an immunohistochemistry method was utilized to explore the expression levels of CLDN9 and p-Stat3 in the HCC tissues and histologically non-neoplastic hepatic tissues.Results: We confirmed that the expression of CLDN9 significantly enhanced the metastatic ability of hepatocytes in vitro, and the activation of the Stat3 pathway by Tyk2 was an important mechanism by which CLDN9 promoted hepatocyte aggressiveness in HCC.Conclusion: As an HCC proto-oncogene, CLDN9 affected the Stat3 signaling pathway via Tyk2 and ultimately enhanced the metastatic ability of hepatocytes.